Serum Vitamin D, Sleep Pattern and Cardiometabolic Diseases: Findings from the National Health and Nutrition Examination Survey - Lo K (Dove Medical Press, 2020)
Kenneth Lo,1,2,* Yu-qing Huang,1,* Lin Liu,1 Yu-ling Yu,1 Chao-lei Chen,1 Jia-yi Huang,1 Ying-qing Feng1 1Department of Cardiology, Guangdong Cardiovascular Institute, Hypertension Research Laboratory, Guangdong Provincial People’s Hospital, Guangdong Provincial Key Laboratory of Coronary Heart Disease Prevention, Guangdong Academy of Medical Sciences, South China University of Technology School of Medicine, Guangzhou, People’s Republic of China; 2Centre for Global Cardiometabolic Health, Department of Epidemiology, Brown University, Providence, Rhode Island, USA*These authors contributed equally to this workCorrespondence: Kenneth Lo; Ying-qing FengDepartment of Cardiology, Guangdong Cardiovascular Institute, Hypertension Research Laboratory, Guangdong Provincial People’s Hospital, Guangdong Provincial Key Laboratory of Coronary Heart Disease Prevention, Guangdong Academy of Medical Sciences, South China University of Technology School of Medicine, Guangzhou, People’s Republic of ChinaTel +86-13147550252Email kenneth_lo@brown.edu; 651792209@qq.comObjective: Although poor sleep health and vitamin D deficiency may be associated with diabetes and hypertension, whether this association shows a trend depending on vitamin D concentration is unclear.Subjects and Methods: We analyzed data from 10,742 participants (4997 men) from the 2007– 2014 National Health and Nutrition Examination Survey. Abnormal sleep pattern (ie, short sleep duration, sleep complaint, and/or sleep disorder), lifestyle factors, serum vitamin D level, and the status of diabetes and hypertension were assessed. Logistic regression was performed to estimate the odds ratio (OR) and 95% confidence interval (CI).Results: Serum vitamin D significantly interacted with short sleep duration and abnormal sleep pattern (both p = 0.003) on the association with diabetes in men. Short sleep duration (OR: 1.82, 95% CI = 1.29, 2.57) and abnormal sleep pattern (OR: 1.95, 95% CI = 1.38, 2.77) were associated with diabetes in men with serum vitamin D of > 75 nmol/L. Serum vitamin D significantly interacted with sleep complaint on the association with hypertension in men and women (both p < 0.05). The magnitude of association between sleep complaint and hypertension in men was stronger when serum vitamin D level was < 50 nmol/L (OR: 2.26, 95% CI = 1.57, 3.25) than when the level was > 75 nmol/L (OR: 1.28, 95% CI = 0.90, 1.83). Similarly, the magnitude of association between sleep complaint and hypertension in women was stronger when serum vitamin D level was < 50 nmol/L (OR: 2.09, 95% CI = 1.53, 2.86) than when the level was > 75 nmol/L (OR: 1.64, 95% CI = 0.98, 2.72). No significant interactions were observed between serum vitamin D level and other sleep variables.Conclusion: Abnormal sleep pattern is associated with a high risk of diabetes and hypertension. The relationship between sleep complaint and hypertension may be strong in people with vitamin D deficiency, and this observation should be verified by prospective studies.Keywords: vitamin D, sleep, diabetes, hypertension, epidemiology